Automated analysis of morphological change in the duodenal mucosa of children with coeliac disease. Issue 11 (November 1981) - Tulloh, E A M; Baylis, J M; Challacombe, D N
Abstract : A modular image analysing system was used to study the morphology of the duodenal mucosa in children with coeliac disease and to compare it with normal duodenal biopsies. The results suggest that this automated method of tissue analysis is useful for the routine analysis of small intestinal biopsies.